Distributional changes in the gender wage gap in the post-apartheid South African labour market - Jacqueline Mosomi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This paper investigates the evolution of the gender wage gap in South Africa, using the 1993-2015 Post-Apartheid Labour Market Series data set. The changes in the gap are heterogeneous across the wage distribution. There has been a substantial narrowing of the gap at the bottom of the distribution, attributable to the implementation of the minimum wage in low-paying industries However, the median gender wage gap is substantial at 23-35 per cent. This is unexplained by differences in human capital characteristics, and is not declining over time. This implies that wage-employed women in South Africa have better human capital characteristics than men. Contrary to previous literature, the wage gap at the mean narrowed from 40 per cent in 1993 to 16 per cent in 2014. The gap at the 90th percentile declined during 1993-2005, but has expanded in recent years. This is due to a continually expanding unexplained component of the wage gap, which is usually associated with discrimination.
Keywords: J16; J31; J71; 330; labour force participation; gender wage gap; discrimination; decomposition; unconditional quantile regression; post-apartheid South Africa